1976
DOI: 10.1042/bj1570521
|View full text |Cite
|
Sign up to set email alerts
|

Absence of binding of pancreatic and urinary kallikreins to α 2-macroglobulin

Abstract: Pancreatic and urinary kallikreins failed to form the typical serine proteinase complex with alpha2M (alpha2-macroglobulin). Studies were performed to compare this with the binding of trypsin to alpha2M at various molar binding ratios, with the use of Sephadex G-200 gel filtration to separate free and alpha2M-bound enzyme fractions. The subunit conversion was totally absent with pancreatic kallikrein from lhich traces of a binding proteinase had been removed. The lack of binding is believed to be the result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…This usually results in a dose-response curve that is nonparallel to the standard curve, which these authors also re ported [21]. The low recovery of active tissue kallikrein when added to plasma and perito neal fluid in this study, and previously also reported in the rat and human [22,23], indi cates that such complex formation takes place, even though it has been reported that porcine tissue kallikrein does not bind to alpha-macroglobulins [24], However, the larg er recovery of active tissue kallikrein from normal peritoneal fluid compared with plas ma supports the theory of alpha-macroglobulin complexes masking the immunoreactivity, as the level of alpha-macroglobulins in normal porcine peritoneal fluid is only about 10% of that in plasma [11,13]. Furthermore the a Fig.…”
Section: Discussionmentioning
confidence: 45%
“…This usually results in a dose-response curve that is nonparallel to the standard curve, which these authors also re ported [21]. The low recovery of active tissue kallikrein when added to plasma and perito neal fluid in this study, and previously also reported in the rat and human [22,23], indi cates that such complex formation takes place, even though it has been reported that porcine tissue kallikrein does not bind to alpha-macroglobulins [24], However, the larg er recovery of active tissue kallikrein from normal peritoneal fluid compared with plas ma supports the theory of alpha-macroglobulin complexes masking the immunoreactivity, as the level of alpha-macroglobulins in normal porcine peritoneal fluid is only about 10% of that in plasma [11,13]. Furthermore the a Fig.…”
Section: Discussionmentioning
confidence: 45%
“…As confirmed in previous reports (Sumi et al, 1978;Takasugi et al, 1980) and in the present study almost all of the pancreatic kallikrein, which was released from the pancreas into blood, also combined with lIz-macroglobulin in plasma from patients. Conversely, Vahtera & Hamberg (1976) reported that pancreatic or urinary kallikrein could not combine with lIz-macroglobulin. If the findings of Vahtera & Hamberg (1976) are correct, how should we interpret the phenomenon of pancreatic kallikrein being combined with lIzmacroglobulin observed in the present study?…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, Vahtera & Hamberg (1976) reported that pancreatic or urinary kallikrein could not combine with lIz-macroglobulin. If the findings of Vahtera & Hamberg (1976) are correct, how should we interpret the phenomenon of pancreatic kallikrein being combined with lIzmacroglobulin observed in the present study? Vahtera & Hamberg (1976) also reported that, if pancreatic or urinary kallikrein could combine with lIz-macroglobulin, the complex-formation might be due to contamination with another proteinase in the kallikrein preparation.…”
Section: Discussionmentioning
confidence: 96%
“…The protein complex contained 13.4 gg trypsin indicating that an equimolar complex was formed. This was further sustained by the recovery of trypsin in the complex [3,24].…”
Section: Trypsin Binding Activity Of Synovial Ohmmentioning
confidence: 87%
“…As seen in Table 5 the bradykinin releasing effect of trypsin is blocked by complex formation with cr2M. In earlier studies we have shown the absence of binding of pancreatic and urinary kallikreins to a2M [24]. Another possibility to prevent proteinase binding would be the blocking of binding sites in E,UTION VOLUME (m0 .…”
Section: Synovial Kininogen and Bradyldnin Releasementioning
confidence: 89%